(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Tampubolon K, Purba E, Basyuni M, Hanafiah DS. 2019. Glyphosate resistance of Eleusine indica populations from North Sumatra, Indonesia. Biodiversitas 20: 1910-1916. Controlling of Eleusine indica populations in oil palm plantations using a similar mode of action of herbicide may cause resistant weed. Overall E. indica populations from oil palm plantations in North Sumatra, Indonesia have never been reported to be glyphosate-resistant. This research was aimed to determine the survival percentage and to classify the resistance of E. indica to glyphosate from oil palm plantations in 11 districts in North Sumatra Province. The research was conducted in the Weed Research Center Field Laboratory, Faculty of Agriculture, Universitas Sumatera Utara from October 2016 to August 2017. This research was arranged in a Randomized Block Design with the glyphosate-treatment using a recommended dose of two l ha-1 and three replications. The ESU0 population was collected in the soccer field of Politeknik Negeri Medan (Medan city) was used as a check, and has never been exposed to the herbicide. Parameters were analyzed using one-way ANOVA, and the means were compared using DMRT at a probability level of 5%. The results showed that 276 (65.56%) of 421 populations were classified as glyphosate-resistant, 88 populations (20.90%) were classified as glyphosate-resistant developing, and 57 populations (13.54%) were classified as glyphosate-susceptible. The highest range of dry weight of glyphosate-resistant E. indica populations were found in 5 districts including South Labuhanbatu District followed by the Serdang Bedagai, Simalungun, Asahan, and North Labuhanbatu Districts. The observed resistance level and dry weight range in the present study indicated the failure in controlling E. indica due to continued use of glyphosate and the potency of E. indica distribution into other oil palm estates due to its high biomass production capability.